2019
DOI: 10.1111/jzs.12336
|View full text |Cite
|
Sign up to set email alerts
|

A complex species complex: The controversial role of ecology and biogeography in the evolutionary history of Syllis gracilis Grube, 1840 (Annelida, Syllidae)

Abstract: The cryptic diversity in the polychaete Syllis gracilis Grube, 1840, in the Mediterranean Sea was examined with an integrative morpho-molecular approach. Individuals of S. gracilis were collected at eleven Mediterranean localities to provide an insight into the role of brackish environments in inducing cryptic speciation. The examination of morphological features combined with a molecular genetic analysis based on a partial sequence of the 16S rRNA gene highlighted discrepancies between morphological and molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The material identified as Syllis gracilis may correspond to a different related species because there are increasing evidence that this species complex includes several cryptic and pseudo-cryptic lineages ( e.g. , Álvarez Campos, Giribet & Riesgo, 2017 ; Langeneck et al, 2020 ). Sphaerosyllis brasiliensis was originally described from colonies of M. hispida from islands off the coast of São Paulo southeastern Brazil ( Nogueira, San Martín & Amaral, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…The material identified as Syllis gracilis may correspond to a different related species because there are increasing evidence that this species complex includes several cryptic and pseudo-cryptic lineages ( e.g. , Álvarez Campos, Giribet & Riesgo, 2017 ; Langeneck et al, 2020 ). Sphaerosyllis brasiliensis was originally described from colonies of M. hispida from islands off the coast of São Paulo southeastern Brazil ( Nogueira, San Martín & Amaral, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the current molecular information available for O. brunnea comes from an Australian individual (electronic supplementary material, table S2), and thus, we decide not to take any taxonomic action until new fresh material can be collected from the type locality in Madeira. Given the amount of putative worldwide distributed species in the subfamily Syllinae that have resulted to be a complex of different species with restricted geographical distributions [ 10 , 20 , 55 ], any taxonomic action in this group should always be based in analyses that include material from the type locality. Finally, our phylogenetic results place the species Syllis laiae n. sp.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental features could be an explanation for this variation. In the Syllis gracilis Grube, 1840 complex (Langeneck et al, 2020), a univariate analysis of morphological characters showed that marine specimens sampled on intertidal algal communities are differentiated from brackish-water and Sabellaria-associated individuals.…”
Section: Pigmentation Data the Essc And Morphological Stasismentioning
confidence: 99%